Assessing users' perception and current practice of facility management in an academic institution - Moe Theint Phyu; Santoso, Djoen San; Sasaki, Nophea; Ho, Huu Loc; AIT Scholarships (Pathum Thani, Thailand : Asian Institute of Technology, 2023)
A higher educational institution is a diverse surrounding with the aim of providing a quality surrounding that fulfills the requirement of its most central users in a productive way. The facility resources and management of the university play a vital function while supporting the university{u2019}s objectives involves offering users versatile learning settings and robust, efficient infrastructure, which serve as essential cornerstones for the university{u2019}s operations. Factors related to indoor environmental quality, power supply and appliances, internet connection, interior and exterior decoration, sitting layout and quality of furniture, water and sanitation, safety, and maintenance of building facilities are considered in this study. The primary objectives of this study were to examine the elements impacting the contentment of both students and staff members regarding the physical amenities and to propose recommendations to enhance the quality of service of the facility management of the institution. The data were collected from 166 respondents during the 2023 Spring semester. According to the results, occupants primarily appreciated the overall facilities provide, however, showed their concerns more on the quality of water and hygiene and cleanliness of water drinking fountain, quality of domestic water, cleanliness of facilities, availability and accessibility of dustbins, waste collection, quality of furniture, Wifi service, quality and decoration of the exterior and interior design of the buildings, regular maintenance and safety measure of the buildings. The facility management of the institution is advised on improving the frequency of inspection of facilities while enhancing preventative maintenance rather than relying solely on corrective measures. This study aids in understanding the progress of an institution's operation and maintenance management factors and improved service quality of the campus through satisfaction among students and staff.
A thesis submitted in partial fulfilment of the requirements for the degree of Master of Engineering in Construction, Engineering and Infrastructure Management, School of Engneering and Technology
Thesis (M. Eng.) - Asian Institute of Technology, 2023
Keywords: Facility management -- Thailand; College facilities -- Thailand